'Ironman': Joseph Daniels and the white history of South Africa's deep south. (September 2015) - van Sittert, Lance
ABSTRACT Polar history has historically been white history, nowhere more so than in South Africa, The recent attempt to imagine a post-apartheid deep south through the public recovery of a black boatman who drowned in the annexation of the Prince Edward Islands in 1948 has ironically left the white history largely intact. Re-reading the annexation not as ceremony and survey, but as labour calls the central claims of this white history into question; that the annexation was a triumph of white seamanship not black stevedoring; that Daniels' death was a tragic accident not a result of racism; and that black labour was merely the manual appendage to white intellects. It reveals that the landing of 300 tons of cargo by black boatmen. was what enabled the 'effective occupation' of the islands. Daniels death was the avoidable result of an institutional racism that discounted the lives of black labour and exposed them at Marion Island to the dangerous work conditions of long hours in open boats in rough sea without adequate safety provisions; and that Daniels was a boatman, not an 'unskilled labourer', with a tradition of co-adventuring that valued an individual for their strength, skill and courage, not the colour of their skin and in which the individual was defined by their contribution to the group